Proceedings of the Ninth ACM International Conference on Web Search and Data Mining 2016
DOI: 10.1145/2835776.2835842
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Predicting Learning Behavior in MOOCs

Abstract: Massive Open Online Courses (MOOCs), which collect complete records of all student interactions in an online learning environment, offer us an unprecedented opportunity to analyze students' learning behavior at a very fine granularity than ever before.Using dataset from xuetangX, one of the largest MOOCs from China, we analyze key factors that influence students' engagement in MOOCs and study to what extent we could infer a student's learning effectiveness. We observe significant behavioral heterogeneity in st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
88
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(90 citation statements)
references
References 22 publications
0
88
0
2
Order By: Relevance
“…The increased use of SPOC forums has contributed to the generation of massive interactive data in higher education. Within the forum data, the hidden engagement patterns involving interactive behaviors and emotional states have been considered as critical factors indicating learning performance (Kent, Laslo, & Rafaeli, 2016;Phan, McNeil, & Robin, 2016;Qiu et al, 2016;Tucker, Pursel, & Divinsky, 2014;Yang, Kraut, & Rosé, 2016;Yang, Wen, Howley, Kraut, & Rose, 2015). Especially, interactive postings and average depth in threads were considered to be correlated with examination' grades (Kent et al, 2016).…”
Section: Student' Engagement In Course Forumsmentioning
confidence: 99%
“…The increased use of SPOC forums has contributed to the generation of massive interactive data in higher education. Within the forum data, the hidden engagement patterns involving interactive behaviors and emotional states have been considered as critical factors indicating learning performance (Kent, Laslo, & Rafaeli, 2016;Phan, McNeil, & Robin, 2016;Qiu et al, 2016;Tucker, Pursel, & Divinsky, 2014;Yang, Kraut, & Rosé, 2016;Yang, Wen, Howley, Kraut, & Rose, 2015). Especially, interactive postings and average depth in threads were considered to be correlated with examination' grades (Kent et al, 2016).…”
Section: Student' Engagement In Course Forumsmentioning
confidence: 99%
“…Massive Open Online Courses (MOOCs) have become an alternative educational platform that allows learners from dispersed geographic locations access the same quality of learning through the web [1]. Coursera, HarvardX, and Khan Academy are some examples of MOOCs.…”
Section: Introductionmentioning
confidence: 99%
“…Coursera, HarvardX, and Khan Academy are some examples of MOOCs. Since 2012, MOOCs modalities have received widespread usage by top Universities [1]. Investigations undertaken by such institutions indicated that the use of MOOCs have attracted many participants towards engagement in the space of courses offered, due to the removal of financial, geographical, and educational barriers [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The "China Basic Education Big Data Development Blue Book (2015)" Conference and Education Big Data Summit Forum held in Beijing Normal University in 2016 [2]. In addition, according to the statistics, Coursera, edX, and Udacity which are three pioneer MOOC platforms provide thousands of courses and draw more than 100,000 registrants each course [5,6]. And Tsinghua University also officially launched the first Chinese version of the MOOC platform -"xuetangX" [4,8].…”
Section: Introductionmentioning
confidence: 99%